The impact of brands on balance sheets in Australia and New Zealand: The effect of IAS 38 - Liang, Li (Leon) (Auckland University of Technology, 2006)
The recognition of brands on companies’ balance sheets as identifiable intangible assets has developed in financial reporting and has been increasingly important since the 1980s. Yet there exists a research gap concerning the impact of brands on balance sheets for Australian and New Zealand companies, especially when the International Accounting Standard 38 equivalent standards are coming into effect from the beginning of 2005 in Australia and of 2007 in New Zealand. A descriptive study has been adopted to analyse the top 50 listed companies in Australia and New Zealand together with the top 50 listed UK companies, where an IAS 38 equivalent standard has already been implemented, as a benchmark. The results show that Australian and New Zealand companies have commonalities and discrepancies in terms of contents and characteristics of brands on balance sheets and the brands valuation methods are normally not reported for both countries. Moreover, some ratio differences with and without the brands can be explained by the heavy brand weightings and excessive brand values to book equity values, and it may be expected that Australian and New Zealand companies will adopt similar brand accounting treatments to those currently used by UK companies.
Keywords: Brand name products; Accounting -- Standards